Global Existence of Solution for the Fisher Equation via Faedo–Galerkin’s Method - Ahmed Hamrouni (Hindawi Limited, 2021)
In this study, we consider the Fisher equation in bounded domains. By Faedo–Galerkin’s method and with a homogeneous Dirichlet conditions, the existence of a global solution is proved.